Exposure of high-density porous polyethylene (Medpor®) used for contour restoration and treatment - K. Sevin,* I. As¸kar, A. Saray, E. Yormuk (Blackwell Synergy, 2000)
Head and neck reconstruction is difficult and often requires complex solutions to restore function and cosmesis. Autogenous tissues are usually preferred, but various alloplasts have been investigated. However, these materials are foreign bodies and most alloplasts tolerate infection and exposure poorly.